2004
DOI: 10.1007/s10147-004-0401-9
|View full text |Cite
|
Sign up to set email alerts
|

Invasive ductal carcinoma within a fibroadenoma of the breast

Abstract: A rare case of invasive ductal carcinoma within a fibroadenoma of the breast in a 42-year-old woman is reported. The patient had a well-defined mass, measuring 6.0 x 5.0 cm, in the upper lateral quadrant of the left breast. Physical examination suggested fibroadenoma. Ultrasonography and mammography revealed some malignant findings. Needle biopsy demonstrated fibroadenoma. Frozen section revealed invasive ductal carcinoma, scirrhous type, arising in a fibroadenoma; muscle-preserving mastectomy was performed. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 9 publications
1
33
0
1
Order By: Relevance
“…Therefore, histological diagnosis is typically unexpected (1,8,9,13,14). The mean age of patients with carcinoma in FA has been reported as 42-44 years, ~20 years subsequent to the peak age of occurrence of FA (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, histological diagnosis is typically unexpected (1,8,9,13,14). The mean age of patients with carcinoma in FA has been reported as 42-44 years, ~20 years subsequent to the peak age of occurrence of FA (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant transformation within FA is unusual, reported to be 0.1-0.3% in a screened population. However, the number of real cases appears to be even rarer; histological diagnosis is typically unexpected following excision of a breast lesion, with only >100 cases reported in the literature thus far (8,9). Classic lobular carcinoma in situ (LCIS) is a type of lobular neoplasia and is diagnosed when >50% of the acini of a lobular unit are distended and distorted by a dyshesive proliferation of cells with small, and uniform nuclei (10).…”
Section: Introductionmentioning
confidence: 99%
“…13 As described earlier, invasive and in situ carcinoma may rarely be seen associated with fibroadenoma ( Figure 4). [3][4][5][6]13,15 Although fibroadenomas are considered innocuous, a recent report showed that 22 of 172 PT patients (12.8%) had previous fibroadenoma excisions, 16 and 11 of 36 malignant PT cases (30.6%) had a history of fibroadenoma, 17 raising the possibility that some fibroadenomas may undergo malignant transformation to PTs. Therefore, any atypical epithelial proliferation or unusual stromal alterations within a fibroepithelial tumor on a core needle biopsy should warrant complete excision of the lesion for further evaluation and to rule out associated malignant transformation or PT.…”
Section: Pathology Of Fibroepithelial Tumors Fibroadenomamentioning
confidence: 99%
“…[1][2][3][4] They are the second most common tumours of the breast after carcinoma and the most common benign tumours of the breast in adolescent girls and young women. 1,3 Malignant transformation of fibroadenoma to carcinoma is very rare (equal or less than 0.5%), and the mean age is fifth decade.…”
mentioning
confidence: 99%
“…1,3 Malignant transformation of fibroadenoma to carcinoma is very rare (equal or less than 0.5%), and the mean age is fifth decade. 2,[4][5][6][7] The most common malignant histologic type coexistence with fibroadenoma is lobular carcinoma in situ (66.9%), followed by ductal carcinoma in situ (12.4%), invasive ductal carcinoma (11%), and invasive lobular carcinoma (3.4%). 4 Positive family history, complex fibroadenomas, proliferative disease adjacent fibroadenomas and BRCA mutation are associated with Turkiye Klinikleri J Case Rep 2015;23 (2) fibroadenomas mild increase risk of subsequent breast cancer.…”
mentioning
confidence: 99%